Técnicas de permacultura como tecnologias socioambientais para a melhoria na qualidade da vida em comunidades da Paraíba - Paes, Wellington Marchi (2014)
Permaculture techniques are alternatives that have been developed in order to produce a permanent crop that restores the human being to the environment, taking into account the observation of the natural environment and experimentation, with the intent of improving the various factors that are contributing to the deterioration of life and nature. Thus, it seeks to restore the nature balance s that human actions have broken. The lack of sanitation has brought many negative consequences, both to human health and the environment, so the waste managing, whether solid or liquid, should be among all local governments priorities. Because the investment in peri-urban areas is inferior to the urban ones, actions focused on eliminating the diffused pollution sources like inappropriate domestic waste disposal and its impact are essential. Therefore, this study intended to demonstrate among local communities that cultivation and the solid and liquid wastes could be sustainably combined. Permaculture activities were carried out: in a familiar way with children from the Escola Elementar Nova Vida, in Pitimbu Municipality-PB; solid waste was reused in handmade artifact in the maroon community of Ipiranga, in the Gurugi district, Conde, PB; and deployment of ecological tanks, with banana circles, for the treatment of greywater, in Engenho Velho, and the evapotranspiration tanks (green tanks for blackwater treatment) in the Condomínio Amizade in João Pessoa, PB. Motivating the communities to develop the proposed activities was a challenge, and only a few people participated. However, after the implementation of the activities there was a general feeling of satisfaction among the participants. The goal of this project was the adoption of Environmental Social technics by specific communities that would later on work as models to be copied by other communities. We have achieved the purpose of the project as we noticed that not only the methodologies have improved the communities where they were implemented, but also that those were spread and adopted by other communities, showing the appropriation of these technologies by the people of these communities.